2012
DOI: 10.1210/jc.2011-3454
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Is the Key Determinant of Skeletal Muscle Mitochondrial Function in Type 2 Diabetes

Abstract: Mitochondrial dysfunction is apparent only in inactive longstanding T2DM patients, which suggests that mitochondrial function and insulin resistance do not depend on each other. Prolonged exercise training can, at least partly, reverse the mitochondrial impairments associated with the longstanding diabetic state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 39 publications
2
79
1
Order By: Relevance
“…Recent studies show that mitochondrial dysfunction of diabetic subjects is closely related to lifestyle factors, including diet, physical activity, sleep, and stress. 53,54) Prolonged exercise and diet intervention can reverse, at least partly, the mitochondrial deficiency and improve the metabolic flexibility and insulin sensitivity in patients with T2DM. 54,55) Recently, dietary PQQ supplementation has been revealed to enhance mitochondrial function and biogenesis and improve metabolic homeostasis in mice and rats.…”
Section: Anti-diabetic Effectsmentioning
confidence: 99%
“…Recent studies show that mitochondrial dysfunction of diabetic subjects is closely related to lifestyle factors, including diet, physical activity, sleep, and stress. 53,54) Prolonged exercise and diet intervention can reverse, at least partly, the mitochondrial deficiency and improve the metabolic flexibility and insulin sensitivity in patients with T2DM. 54,55) Recently, dietary PQQ supplementation has been revealed to enhance mitochondrial function and biogenesis and improve metabolic homeostasis in mice and rats.…”
Section: Anti-diabetic Effectsmentioning
confidence: 99%
“…Conversely, two separate lines of muscle-specific Pgc1a (Ppargc1a) transgenic mice displayed a significant enhancement in the markers of mitochondrial content and yet were insulin resistant due to excessive FA delivery and reduced GLUT4 (SLC2A4) expression in muscle (Miura et al 2003, Choi et al 2008. A growing number of studies in humans have also reported intact mitochondrial function in various insulin-resistant populations (De Feyter et al 2008, Trenell et al 2008, Lefort et al 2010, van Tienen et al 2012, Fisher-Wellman et al 2013. Collectively, these studies suggest that mitochondrial dysfunction in muscle is not an obligatory factor required for the accumulation of intramuscular lipids and the development of insulin resistance.…”
Section: Mitochondrial Dysfunction Reactive Oxygen Species and Insulmentioning
confidence: 99%
“…In line with the microarray studies noted above, mRNA levels for a variety of mitochondrial genes have been shown to be reduced in muscle biopsies obtained from various insulin resistant populations, including lean insulin-resistant offspring of patients with T2D [80], obese subjects [81], patients with polycystic ovarian syndrome [82] and subjects with estab-lished T2DM [83,84]. The level of mtDNA was also shown to be lower in both obese, insulin resistant subjects and obese subjects with T2D [85,86].…”
Section: Mitochondrial Dysfunction In Muscle and Its Association Withmentioning
confidence: 72%
“…A similar finding was reported in a separate population where post-exercise phosphocreatine recovery indicated similar mitochondrial function between obese patients in either the early or advanced stages of T2D and normoglycemic controls matched for age, body composition and habitual physical activity levels [187]. A further study from the same group also recently reported similar in vivo mitochondrial function with MRS in prediabetic subjects compared with age, BMI and activity-matched controls, despite the presence of insulin resistance (by HOMA-IR and OGTT) [83]. In young lean men born with low birth-weight, mitochondrial function by MRS and mitochondrial gene expression are intact, despite these subjects displaying several pre-diabetic characteristics [188].…”
Section: Human Studiesmentioning
confidence: 77%